Constraining convection across the AGB with high-angular-resolution observations. Issue Volume 14:Issue S343(2019) (August 2018) - Paladini, Claudia; Baron, Fabien; Jorissen, A.; Le Bouquin, J.-B.; Freytag, B.; Van Eck, S.; Wittkowski, M.; Hron, J.; Chiavassa, A.; Berger, J.-P.; Siopis, C.; Mayer, A.; et al.
Abstract: We present very detailed images of the photosphere of an AGB star obtained with the PIONIER instrument, installed at the Very Large Telescope Interferometer (VLTI). The images show a well defined stellar disc populated by a few convective patterns. Thanks to the high precision of the observations we are able to derive the contrast and granulation horizontal scale of the convective pattern for the first time in a direct way. Such quantities are then compared with scaling relations between granule size, effective temperature, and surface gravity that are predicted by simulations of stellar surface convection.